Determinación de la huella ecológica mediante datos estadísticos durante la pandemia por el covid-19 en la provincia de Cotopaxi, en el periodo 2020-2021. - López Ramos, Arleth Marisol (2021)
Ecuador ranks 67th out of 151 countries in the global ecological footprint ranking with 2.2 hga, while Cotopaxi is a province with a large amount of natural resources, due to its climatic diversity, it offers a variety of products. However, environmental sustainability can be affected by irresponsible consumption of natural resources. The research determined the ecological footprint during the covid-19 pandemic (2020-2021) in the province of Cotopaxi, using the ecological footprint calculator belonging to the Global Foodprint Network. The results show that the ecological footprint (4.48hga) in the province of Cotopaxi was not reduced in the period 2020-2021, due to the effects of the pandemic and on the contrary has increased considerably compared to the national average of 2013 (1.57hga). Being the cantons Pangua (5.19 hga), Latacunga (4.77 hga), Salcedo (4.62 hga) those with the highest values in the province. The cantons with the highest CO2 emissions were Pangua (7.55 hga), Pujilí (7.29 hga) and Latacunga (6.94 hga). Additionally, it was found that there is a positive correlation between variables that affect the land type dimension of consumption and the ecological footprint for the canton of Latacunga, with a confidence greater than 99% as the p-value was less than 0.01. Similarly, in the cantons of La Maná, Pangua, Salcedo, Saquisilí and Sigchos, there is a positive correlation between the same variables with a confidence greater than 95%.